Trade and payments theory in a financialized economy - Michael Hudson (Levy Economics Institute of Bard College, 2011)
Ricardian trade theory was based on the cost of labor at a time when grain and other consumer goods accounted for most subsistence spending. But today's budgets are dominated by payments to the finance, insurance, and real estate (FIRE) sector and to newly privatized monopolies. This has made FIRE the determining factor in trade competitiveness. The major elements in US family budgets are housing (with prices bid up on credit), debt service, and health insurance - and wage withholding for financializing Social Security and Medicare. Industrial firms also have been financialized, using debt leverage to increase their return on equity. The effect is for interest to increase as a proportion of cash flow (earnings before interest, taxes, depreciation, and amortization, or EBITDA). Corporate raiders pay their high-interest bondholders, while financial managers also are using EBITDA for stock buybacks to increase share prices (and hence the value of their stock options). Shifting taxes off property and onto employment and retail sales spurs the financialization of family and business budgets as tax cuts on property are capitalized into higher bank loans. Payments to government agencies for taxes and presaving for Social Security and Medicare absorb another 30 percent of family budgets. These transfer payments to the FIRE sector and government agencies have transformed international cost structures, absorbing roughly 75 percent of US family budgets. This helps explain the deteriorating US industrial trade balance as the economy has become financialized.
Keywords: F3; F4; F10; F17; F18; F37; G12; G21; H21; J61; 330; international trade theory; financialization